2022
DOI: 10.12669/pjms.38.3.4283
|View full text |Cite
|
Sign up to set email alerts
|

Subchorionic hematoma and pregnancy outcomes in patients with threatened miscarriage

Abstract: Objective: To compare maternal and perinatal outcomes in patients with threatened miscarriage with or without subchorionic hematoma (SCH) at a tertiary care hospital. Methods: This retrospective cohort study was conducted at Aga Khan University Hospital. The study included 200 patients of <20 weeks singleton pregnancy with threatened miscarriage from January 2016 till December 2018. These patients were divided into two groups based on the presence (study group) or absence of subchorionic hematoma (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Our data suggest that SCH presenting in the first trimester does not adversely affect neonatal outcomes, similar to the conclusions of several current studies. [7,21] However, some studies [22] have found that the presence of SCH can lead to an increased risk of small gestational age infants. At present, there is no consensus on the relationship between SCH and adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that SCH presenting in the first trimester does not adversely affect neonatal outcomes, similar to the conclusions of several current studies. [7,21] However, some studies [22] have found that the presence of SCH can lead to an increased risk of small gestational age infants. At present, there is no consensus on the relationship between SCH and adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In addition, they may also be related to the following factors: abnormal coagulation function, immune and endocrine disorders, obesity, recurrent induced abortion, hypertension, and/or the use of aspirin or other anticoagulants, among which immune factors are the most closely related. [ 11 , 12 ] The patient in this case had 3 induced abortions and used aspirin enteric coated tablets and enoxaparin needles in the early treatment, both of which are susceptible factors for the occurrence of MTH.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmunity mainly includes anticardiolipin antibodies and antibodies β Abnormalities such as 2 glycoprotein antibodies and lupus anticoagulants: Studies have found that the titers of these 3 antibodies in MTH patients are significantly higher than those in normal pregnant patients, indicating that the presence of autoantibodies and pre thrombotic state can disrupt the stability of the mother fetal interface, leading to decidual immune vasculitis, intravascular microthrombosis, decidual vascular rupture, abnormal invasion of the trophoblast, and rebleeding after ischemia-reperfusion. [ 11 ] Experimental studies have shown that Panax notoginseng has the effects of shortening clotting time, increasing platelet production, increasing platelet aggregation, improving clotting ability, and repairing the endometrium. Endometrial tissue factor is involved in the process of uterine bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[6][7][8] There are conflicting reports in the literature on the significance of SCH in early pregnancy. [7][8][9][10][11] However, the presence of SCH in pregnancy may increase the risk of miscarriages and adverse maternal and perinatal outcomes. [7][8][9][10][11] Therefore, this research aimed to determine the prevalence of AM and the relationship between AM and SCH in the Niger Delta region of Nigeria, where the study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] However, the presence of SCH in pregnancy may increase the risk of miscarriages and adverse maternal and perinatal outcomes. [7][8][9][10][11] Therefore, this research aimed to determine the prevalence of AM and the relationship between AM and SCH in the Niger Delta region of Nigeria, where the study was conducted. The sample size for this study was calculated using the formula: n = z 2 pq/d 2 [12] Where: n = minimum sample size z = normal standard deviation set at 95% confidence limit = 1.96 p = proportion of women in the target population with subchorionic haematoma, which is 50% (50% = 0.5).…”
Section: Introductionmentioning
confidence: 99%